Teologi Kebenaran Tuhan Perspektif Sifat Salbiyah di Kalangan Ahlussunnah Wal Jam’aah - Abdurrohman Al Asy’ari (Pusat Riset dan Inovasi Nasional, 2022)
The research seeks to reveal the perspective of the truth about God, is library research with a philosophical inquiry approach. Primary data sources are from the Al-Qur'an and hadith, strengthened by secondary data from other literature, then analyzed for interpretation, comparison and reflection. The research resulted in the conclusion: Proving the truth of God is not only a topic of discussion for Western philosophers, but also Muslim philosophers and theologians, such as Muslim philosophers and theologians who were followers of the Mu'tazilah and al-Ash'ariyah. This proof is divided into two propositions, First, Argument a novitate mundi (dalil al-huduts), which emphasizes the temporality of the universe, and has actually been used popularly by Muslim theologians with a general procedure, proving the temporality of the universe, second, the postulate of possibility (dalil al-imkan), focuses on arguments from contingency. These two proofs confirm that God is real. In this way, the thoughts of Muslim philosophers increasingly strengthen the existence of the reality of God. After the formula for the nature of salbiyah is applied to all Gods, it can be seen that all Gods are void Gods, except Allah SWT who is true.